Highly Selective Tau-SPECT Imaging Probes for Detection of Neurofibrillary Tangles in Alzheimer’s Disease - Ono, Masahiro (Sci Rep, 2016)
Neurofibrillary tangles composed of aggregates of hyperphosphorylated tau proteins are one of the neuropathological hallmarks of Alzheimer’s disease (AD) in addition to the deposition of β-amyloid plaques. Since the deposition of tau aggregates is closely associated with the severity of AD, the in vivo detection of tau aggregates may be useful as a biomarker for the diagnosis and progression of AD. In this study, we designed and synthesized a new series of radioiodinated benzoimidazopyridine (BIP) derivatives, and evaluated their utility as single photon emission computed tomography (SPECT) imaging agents targeting tau aggregates in AD brains. Five radioiodinated BIP derivatives were successfully prepared in high radiochemical yields and purities. In in vitro autoradiographic studies using postmortem AD brains, all BIP derivatives displayed high accumulation of radioactivity in the brain sections with abundant neurofibrillary tangles, while no marked radioactivity accumulation was observed in the brain sections with only β-amyloid aggregates, indicating that the BIP derivatives exhibited selective binding to tau aggregates. Biodistribution studies in normal mice showed high brain uptake at 2 min postinjection (3.5–4.7% ID/g) and rapid clearance at 60 min postinjection (0.04–0.23% ID/g), which is highly desirable for tau imaging agents. The results of the present study suggest that [(123)I]BIP derivatives may be useful SPECT agents for the in vivo imaging of tau aggregates in AD.